TOXIC ROMANTIC RELATIONSHIP PORTRAYED IN AFTER WE COLLIDED NOVEL OF ANNA TODD - Kartosugondo, Susan; Winardi, Yohanes Kurniawan; Fadilah, Eka (Seminar Nasional Ilmu Terapan, 2023)
This research aims to explore the signs of a toxic relationship in the novel "After We Collided" by Anna Todd and the negative impacts resulting from such toxicity. This research focuses on the two main characters, Tessa and Hardin’s complex relationship. Morgan Lee's theory of signs of toxic relationships was used to discover the signs of the toxic relationship in the narrative. The Interpretive-Qualitative approach is used to analyze this research. The novel's listed utterances and narrations served as the primary data source. The data was collected through reading and understanding the whole novel, then it was analyzed the according to the statement of problems and research questions. In analyzing the data, the conversations between the main characters and other characters were used to show the signs and the impact of a toxic romantic relationship between the main characters. The findings of this study reveal that the main character's relationship is afflicted by toxicity, which severely impact both characters' well-being.